ANALISA PENYALURAN KREDIT USAHA RAKYAT TERHADAP KINERJA CICILAN DAN KINERJA USAHA UMKM (Studi Kasus pada Bank Riau Kepri) - Elisa, Verina Elisa; Purwoko, Bambang; W. Sumarlin, Antonius (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2017)
The purpose of this research is to know the role of assistance provided by the creditor to the debtor in generating a combination of bank's corporate strategy and business strategy of UMKM benefiting both parties. The research was conducted in several locations of MSMEs that were built by Bank Riau Kepri. The sampling technique was done by purposive sampling. Data analysis using Structural Equation Model (SEM) method with data processing using SMART PLS3. The results showed that there was a positive relationship between the performance of UMKM repayments on the performance of MSMEs. Although KUR with single-digit interest was shown to assist MSMEs in improving their business performance, the results of this study still showed the same KUR channeling bank as other credit products issued by the bank.